Evolution of community health workers: the fourth stage - Mor, Nachiket; Ananth, Bindu; Ambalam, Viraj; Edassery, Aquinas; Meher, Ajay; Tiwari, Pearl; Sonawane, Vinayak; Mahajani, Anagha; Mathur, Krisha; Parekh, Amishi; Dharmaraju, Raghu (Frontiers in Public Health, 2023)
Comprehensive primary care is a key component of any good health system. The classical British GP model, because of severe challenges of physician availability, is all but infeasible for most developing countries, and there is an urgent need to evolve a new approach which offers comparable, possibly even superior, outcomes through the use of community health workers (CHWs). We suggest that there are potentially four stages in the evolution of the CHW – the health messenger, the physician extender, the focused provider, and the comprehensive provider. In the latter two stages, the physician becomes much more of an adjunct figure, unlike in the first two, where the physician is at the centre. We study the comprehensive provider stage (the fourth stage) using Qualitative Comparative Analysis (QCA) to analyse six CHW programs. Starting with the four Starfield principles, we arrive at seventeen potential factors that could be important. Based on a careful reading of the programs, we then ascertain which of the seventeen are important and arrive at a truth table from which we attempt to simultaneously determine which factors are important and how close each program is to delivering on them. Our analysis suggests that all seventeen factors are important but in varying degrees and that the Alaskan, Iranian, Dvara Health, and Swasthya Swaraj programs incorporate more than 80% (> 14) of them already. Of the seventeen factors, there are six that are present in all the six programs discussed in this study and could be considered foundational for the establishment of an effective fourth-stage CHW program. These include (i) close supervision of the CHW; (ii) care coordination for treatment not directly provided by the CHW; (iii) defined referral pathways to be used to guide referrals; (iv) medication management which closes the loop with patients on all the medicines that they need both immediately and on an ongoing basis (this is the only component which needs engagement with a licensed physician); (v) proactive care: which ensures adherence to treatment plans; and (vi) cost-effectiveness in the use of scarce physician and financial resources.